Analisis Keterampilan Proses Sains Siswa Kelas XI IPA SMA Negeri 2 Pangkajene dalam Model Pembelajaran Inkuiri Terbimbing (Studi pada Materi Titrasi Asam Basa) - Faisal Faisal (ChemEdu, 2020)
This pre-experimental research aims to describe the student’s science process skill in guided inquiry learning model in the subject matter of acid and base titration. The research population were all students of class XI IPA SMA Negeri 2 Pangkajene consist of 4 class were 115 students. The research samples were 29 students of class XI IPA Archimedes SMA Negeri 2 Pangkajene. Science Process Skill data was collected by observation sheet, student worksheet, and lab report was observed during the learning process. The results of the descriptive analysis showed that the average percentage of science process skills of students with 9 indicators (asking questions was 77,01% classified good category, make hypotheses was 56,89% classified not good category, research plan was 100% classified very good category, using tools and materials was 75,82% classified good category, interpreting was 81,35% classified good category, measuring was 66,39% classified enough good category, calculating was 78,46% classified good category, predicting was 60,34% classified not good category and communicate the results was 88,08% classified very good category). Thises mean that the student’s science process skill of class XI IPA SMA Negeri 2 Pangkajene in guided inquiry learning model of the subject matter acid-base titration was 76,04% good category.